The Influence Of Leadership, Motivation, Work Environment On Employee Performance And Quality Services At Royal Prima Hospital Medan 2024 - Aulia, Dinda Rahmah; Nasution, Sri Lestari Ramadhani; Girsang, Ermi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
In implementing quality improvement, there are things that need to be considered so that it can run according to the desired results, such as leadership, work motivation, and work environment which will have an impact on employee performance and will be closely related to the quality of service provided to the public. The purpose of this study is to analyze the influence of leadership, motivation, and work environment on employee performance and service quality at RSU Royal Prima Medan in 2024. This type of research is quantitative and analytical using a cross-sectional research design. The population in this study were employees at RSU Royal Prima Medan consisting of 762 medical and non-medical employees. The sampling technique in this study used Proportional Random Sampling with a sample size of 248. Data analysis used SEM with univariate, bivariate and multivariate analysis. The results showed that the variables of leadership, motivation and work environment influenced employee performance at RSU Royal Prima Medan in 2024 with the most influential variable being the leadership variable (X1). Leadership, motivation and work environment variables influence the quality of service at Royal Prima Medan Hospital in 2024 with the most influential variable being the leadership variable (X1).